EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DAN PRAKTIK CUCI TANGAN PAKAI SABUN (CTPS) PADA SISWA SD - Handayani, Rini; Alia Keumala Muda, Cut; Nurmawaty, Dwi; Rendi Anggara, Taufik (Media Inovasi Pendidikan dan Publikasi, 2023)
Elementary student is one of age group that having high risk to infected. One of preventive action to it is doing clean and healthy behavior and washing hand with soap in school. The aims these activities was to increase student knowledge about doing clean and healthy behavior and washing hand with soap in school. These activities were done in education with lecture and demonstration. The result of these activities is there is score different before and after students had education. It is be recommended to do these activities routinely to student.